Método para análise interna das organizações : uma abordagem a partir da Resource-Advantage Theory - Rossi, Ricardo Messias (Universidade Federal de São Carlos, 2008)
Managers use strategic planning in order to design the ways to get the organizational goals. In a competitive environment the organizations aim to overcome their competitors and to obtain superior financial performance. In order to reach this superior financial performance, the organizations manage their resources so as they can obtain a position of competitive advantage in the marketplace. Thus, the resource management is an important activity in the organizations and the internal analysis is a process that can support this activity. Methods and frameworks to support strategic analyses are no novelty in the business environment. In different intensities these structures of analyses are built up from theoretical knowledge and concepts. In this thesis it is proposed a set of steps to facilitate the strategic competitive planning of organizations. This set of steps was turned into a managerial framework of organizations internal analysis, using the Resource-Advantage Theory as theoretical basis. Thus, the main goal of this thesis was to develop a method, departing from the resource concept, for internal analysis of companies that are embedded in a context of market competition. Exploratory and qualitative research was carried out. Departing from literature review related to the theme, a preliminary method of internal analysis was built then validated and improved by means of collected data from field research. The field research consisted of six case studies with companies working in the area of agrochemicals industry in Brazil. The final version of the internal analysis method is made of six steps. The study contributes theoretically by discussing several concepts related to the Resource-Based Theory and the Resource-Advantage Theory. As a result, the study proposes a way of operationalization of the resource concept (that is a gap observed by some authors). Managerially speaking, the study contributes by providing the administrators with a method of analysis that supports decisions related to organizational resources management.
Keywords: Vantagem competitiva; Planejamento estratégico; Planejamento empresarial; Concorrência; Estratégia; Desempenho organizacional; Administração estratégica; Cadeia de valor; Recursos; Strategic management; Business strategy; Competition; Resources; Value chain; Competitive advantage; ENGENHARIAS::ENGENHARIA DE PRODUCAO